Analysis Of Promotion And Marketing Strategies In The Global Market - Suhairi; Raihan Saputra; Raihan Sultani; Shelvi Fadillah Harahap (International Journal of Economic Research and Financial Accounting, 2023)
Small, micro and medium business competition continues to increase, so efforts are needed. so that MSMEs can maintain the continuity of their business in facing the global market era of the ASEAN Economic Community (AEC). One of the efforts is to improve the strategy that has the lowest risk of failure known as the go-to-market strategy. Globalization is another test for companies when implementing advertising methods. Due to globalization, organizations have to compete with organizations that have large capital and quality assets. So far, Indonesia has become a competitive target market. Globalization and market competition require all executives to focus on the global climate. Advertising is something every business should do. The most important thing in advertising is conveying effective and persuasive messages that attract consumers' attention. This article aims to study advertising and marketing strategies in the global market. This research method uses qualitative methods. The strength of global trade unions in the Indonesian market lies in their ability to develop global marketing strategies adapted to the Indonesian market.